PENGARUH ENTERPRISE RISK MANAGEMENT DISCLOSURE, KINERJA KEUANGAN, DAN REPUTASI AUDITOR TERHADAP NILAI PERUSAHAAN (Studi Empiris Perusahaan Asuransi Yang Go Publik Di Bursa Efek Indonesia Tahun 2010-2013) - Rizka, Ifada Diah Ayu; Arifin, Zaenal (JAB (Jurnal Akuntansi & Bisnis), 2015)
This study aims to determine the effect of Enterprise Risk Management Disclosure, Financial Performance and Auditor Reputation on firm value. The population in this study is an insurance company that go public on the Indonesian Stock Exchange from the year 2010-2013, with 44 samples selected using purposive sampling method. Testing the hypothesis in this study using descriptive statistical analysis and multiple linear regression analysis. The results of this study showed that the variable ERMD, ROA, and LIK does not effect to NP. While the variable LEV with a confidence level of 90% and RP significantly effect to NPL. Keyword:             Risk Management Disclosure, Profitability, Leverage, Liquidity, Auditor Reputation, and Firm Value.